Peacock Paradise The Bird Park: A perspective of promotional strategy in the tourism industry / Ainon Juleani Jameri - Jameri, Ainon Juleani (Faculty of Business Management, 2002)
Malaysia Tourist Promotional Board or Tourism Malaysia is a statutory body established under the Malaysia Tourists Promotional Board Act 1992 where the objectives are to promote Malaysia as an outstanding tourists destination and aim to increase the number of tourists to Malaysia. Therefore it is important that a research of this nature be conducted to ensure that Sahabat Budi Leisure Sdn. Bhd. knows what are their strength, weaknesses, opportunities and threat that they are facing especially in promoting Peacock Paradise The Bird Park, Malacca to its tourists and visitors. To attract tourists and visitors come to PPTBP is to promote this place successfully. The techniques that the researcher used to obtain information from respondents including distribute questionnaires, observations and personal interview. For this study the researcher had distributed 75 questionnaires to the first respondents who comes to PPTBP, Malacca but only 50 questionnaires are completely answered by the respondents. The findings reveal most of people are felt that the promotional campaigns are less effective to make people aware in order to attract tourists and visitors come to PPTBP, Malacca. Some recommendations are suggested where those hopefully could improve promotional strategies for the company.